Energy Efficiency of an LPG-Powered Extended-Range Electric Vehicle - KRAWCZYK, Paweł; KOPCZYŃSKI, Artur; LASOCKI, Jakub (Engineering Transactions, 2025)
This paper deals with energy efficiency evaluation of an extended range electric vehicle (EREV) equipped with a range extender (REX) powered by liquefied petroleum gas (LPG). The investigation is based on simulation, with key input data derived from empirical studies carried out by the authors. It includes four target driving ranges (200, 300, 400, 500 km), six driving cycles (WLTC 3b, FTP-75, CLTC-P, Artemis 130, NYCC, HWFET) and three battery size variants for the WLTC 3b cycle. The influence of the these factors on the overall efficiency and specific energy consumption of the EREV is assessed. The results are analyzed in terms of the number of REX activations per 100 km and the total REX operating time.